A model of criteria system for evaluation of construction contraction agreements - Mitkus, Sigitas; Trinkūnienė, Eva (Business: Theory and Practice, 2007)
Construction contract is one of the steps of the construction process. In order to conclude acceptable and thoughtout construction contracts, effective methodologies for their evaluation and comparison must be developed. In order to solve various legal problems, electronic legal decision support systems have been developed in the world. Application of the electronic legal decision support systems can help to navigate in the legal system easier, makes additional reading of legal acts redundant, creates opportunities to analyse decision variants and to select the most favourable one, provides users with the newest and most extensive information, enables quick search and can use classification and information transfer features. In order to conclude acceptable and well-thought construction contraction agreements, effective methodologies for their evaluation and comparison must be developed. In order to prepare such methodologies, it is necessary to analyse not only technical, organisational and economic aspects in construction but also legal aspects of a construction contraction agreement. Management of construction works includes conclusion of contracts between the client and the contractor. Contract making has great influence on economic success of both parties, on their behaviour in order to increase their profit and it can protect against possible loss. This article analyses construction contraction agreements by providing a model of construction contraction agreement provisions based on their functions. Construction contraction agreements should be concluded, evaluated and compared on the basis of this model. Values of indicators are determined and a multiple criteria decision support system is developed on the basis of this model.